Toripalimab: the First Domestic Anti-Tumor PD-1 Antibody in China - Zhang, Lin; Hao, Bo; Geng, Zhihua; Geng, Qing (Frontiers in Immunology, 2022)
Toripalimab (TuoyiTM) is a selective, recombinant, humanized monoclonal antibody against programmed death protein 1 (PD-1) developed by Shanghai Junshi Bioscience Co., Ltd. Toripalimab is able to bind to PD-1 and block the interaction with its ligands. The binding of toripalimab to PD-1 is mainly attributed to the heavy chain of the former and the FG loop of the latter. Toripalimab received a conditional approval in China for the treatment of melanoma (second-line) in December, 2018. It has also received approvals to treat nasopharyngeal carcinoma (first-line and third-line) and urothelial carcinoma (second-line) in 2021. Additionally, several orphan drug designations were granted to toripalimab by the US Food and Drug Administration. Toripalimab has exhibited primary anti-tumor effects in tumors such as melanoma, lung cancer, digestive tract tumors, hepatobiliary and pancreatic tumors, neuroendocrine neoplasms, nasopharyngeal carcinoma and urothelial carcinoma. It showed a satisfactory anti-tumor effect and long-term survival benefits in Chinese melanoma patients, while the combination of axitinib with toripalimab exhibited an impressive result in metastatic mucosal melanoma. As a checkpoint inhibitor, toripalimab was generally well-tolerated in the enrolled patients. Due to different study populations, comparisons could not be made directly between toripalimab and other drugs in most cases. Nevertheless, the introduction of toripalimab may offer a valuable choice for decision-making in the treatment of tumors in the future.